2019
DOI: 10.1139/cjfas-2017-0472
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing snow crab (Chionoecetes opilio) movements in the Sydney Bight (Nova Scotia, Canada): a collaborative approach using multiscale acoustic telemetry

Abstract: Like many deeper ocean species, the fine-scale movement ecology of snow crab is not well understood. We integrated fine-scale positioning telemetry with larger-scale position estimates from autonomous mobile surveys and harvester returns to evaluate movements of male and female snow crab (Chionoecetes opilio). Effects of life stage–sex, temperature, and diel and tidal cycles on movement velocity were observed, with a tendency for increased velocities during the night, slack tide, and at increasing water temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Recently, ‘tagging effects’ (e.g., elevated activity) have been documented in other crab species (e.g., Snow Crab, Chionoecetes opilio ), which is typically dealt with by discarding detections from the first day of tracking [ 102 , 103 ]. While we found no evidence of changes in activity, tagging effects in crabs may manifest themselves in ways not amenable to visual inspection of activity, such as burial (i.e., seeking refuge) or emigration from the area.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ‘tagging effects’ (e.g., elevated activity) have been documented in other crab species (e.g., Snow Crab, Chionoecetes opilio ), which is typically dealt with by discarding detections from the first day of tracking [ 102 , 103 ]. While we found no evidence of changes in activity, tagging effects in crabs may manifest themselves in ways not amenable to visual inspection of activity, such as burial (i.e., seeking refuge) or emigration from the area.…”
Section: Discussionmentioning
confidence: 99%
“…; Stieglitz and Dujon ; Cote et al. ). When integrated with environmental or physiological sensor tags, acoustic telemetry can provide novel insights into the biology and ecology of tagged animals (e.g., Landry et al.…”
Section: Examples Of How Partnership In Acoustic Telemetry Network Imentioning
confidence: 98%
“…These crab are mainly fished on the east coast, yet their movement ecology is not well understood. By integrating fine-scale positioning telemetry with larger-scale position estimates from autonomous mobile surveys and harvester returns, Côté et al (2019) demonstrated little evidence of site fidelity and no strong environmental influences on movements in this species, suggesting behavioural plasticity of snow crab and relative stability of offshore environments.…”
Section: Atlantic Otnmentioning
confidence: 99%